2017
DOI: 10.1186/s12864-017-4110-y
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and expression analysis reveal the potential role of the HD-Zip gene family in regulation of embryo abortion in grapes (Vitis vinifera L.)

Abstract: BackgroundThe HD-Zip family has a diversity of functions during plant development. In this study, we identify 33 HD-Zip transcription factors in grape and detect their expressions in ovules and somatic embryos, as well as in various vegetative organs.ResultsA genome-wide survey for HD-Zip transcription factors in Vitis was conducted based on the 12 X grape genome (V. vinifera L.). A total of 33 members were identified and classified into four subfamilies (I-IV) based on phylogeny analysis with Arabidopsis, ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 65 publications
0
56
0
Order By: Relevance
“…Its target gene was DlHD-Zip 8 (ATHB8), it was significantly more highly expressed in GE than that in NEC and EC. Zhiqian Li investigated the HD-zip family from the whole-genome analysis of ovules and somatic embryos in grape, and found that HD-zip genes family might regulate seed abortion 60 . However, ATHB8 of the HD-Zip family was induced by auxin in Arabidopsis thaliana, and it was strongly expressed in vascular tissue when embryos developed to the heart embryonic stage 43 .…”
Section: Many Mirnas Are Involved In Early Se In Longanmentioning
confidence: 99%
“…Its target gene was DlHD-Zip 8 (ATHB8), it was significantly more highly expressed in GE than that in NEC and EC. Zhiqian Li investigated the HD-zip family from the whole-genome analysis of ovules and somatic embryos in grape, and found that HD-zip genes family might regulate seed abortion 60 . However, ATHB8 of the HD-Zip family was induced by auxin in Arabidopsis thaliana, and it was strongly expressed in vascular tissue when embryos developed to the heart embryonic stage 43 .…”
Section: Many Mirnas Are Involved In Early Se In Longanmentioning
confidence: 99%
“…By previous research on ZHD family members of other species in plant, we can have a fundmental understanging of ZHD. HD-Zip gene family expression were investigated in regulation of embryo abortion in grapes [31]. However, in order to let us have a further understanding of ZHD TFs.…”
Section: Introductionmentioning
confidence: 99%
“…6a). Common among these were the GCN4 motif and Skn-1 motif related to endosperm expression, TGACG motif and CGTCA motif involved in methyl jasmonate responses, TCA element involved in salicylic acid responses, ABRE element associated with abscisic acid, HSE element involved in heat stress, MBS element related to drought inducibility, TC-rich repeats associated with defense and stress responses, LAMP element and AE-box involved in light response, and 5' UTR Py-rich stretch conferring high transcription levels [27].…”
Section: Deletion Analysis Of the Vvhb58 Promotermentioning
confidence: 99%